PENGARUH HARGA, PROMOSI DAN LOKASI TERHADAP MINAT BELI KONSUMEN DI SUPERMARKET TARAS INDAH BATAM - Imelda Tamba; Dinarti Siburian; Josepin Harianja (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2023)
This study aims to determine the effect of price, promotion and location either partially or simultaneously on consumer buying interest at Taras Indah Supermarket Batam. This research was conducted using quantitative research methods with the number of respondents as many as 90 consumers and data collection using questionnaires. The results of this study found that the multiple linear regression model is Y = 1.684 + 0.146X1 + 0.414X2 + 0.378X3 + e. The results of the study with a significance level of 5% showed that: (1) the price variable had no and no significant effect on consumer buying interest with a tcount of 1.423 < ttable 1.663 and a significance level of 0.158 > 0.05. (2) the promotion variable has a positive and significant effect on consumer buying interest with a tcount value of 3.803 > ttable 1.663 and a significance level of 0.000 <0.05. (3) the location variable has a positive and significant effect on consumer buying interest with a tcount value of 3.895 > ttable 1.663 and a significance level of 0.000 <0.05. And the f test shows that the fcount for price, promotion, and location is 323,175 > ftable 2.71 with a significance level of 0.000 < 0.05. This shows that the variables of price, promotion and location simultaneously have a positive and significant effect on consumer buying interest at Taras Indah Supermarket Batam.